2010
DOI: 10.1002/j.2161-0045.2010.tb00180.x
|View full text |Cite
|
Sign up to set email alerts
|

Applying a Systemic Procedure to Locate Career Decision‐Making Difficulties

Abstract: Locating clients' career decision‐making difficulties is one of the first steps in career counseling. The authors demonstrate the feasibility and utility of a systematic 4‐stage procedure for locating and interpreting career decision‐making difficulties by analyzing responses of 626 college students (collected by Tai, 2007) to the Career Decision‐making Difficulties Questionnaire (CDDQ; Gati, Krausz, & Osipow, 1996). In addition, the responses of 2 students selected from this group are individually analyzed an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
43
1
2

Year Published

2011
2011
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(49 citation statements)
references
References 30 publications
3
43
1
2
Order By: Relevance
“…The CDSES-SF is a valuable aid in identifying these issues, which, we believe, need to be adequately integrated in a wide spectrum process of consulting: From this point of view we agree with Gati and Amir (2010) when they argue that 'it is therefore obvious that there are no substitutes for the career counselor's expert judgment about the intervention sequence, taking into account the client's unique situation and personal traits' (p. 318), and with Osipow (1999) who, referring to Career Decision Making Self-Efficacy Scale (CDMSES) (Taylor & Betz, 1983), emphasizes that it 'can identify those aspects of the career decision-making process itself in which clients may be deficient. Having done that, emphasis in counseling can be placed on helping individuals acquire the skills needed to progress further in their career decision status' (p. 152).…”
Section: 65mentioning
confidence: 62%
“…The CDSES-SF is a valuable aid in identifying these issues, which, we believe, need to be adequately integrated in a wide spectrum process of consulting: From this point of view we agree with Gati and Amir (2010) when they argue that 'it is therefore obvious that there are no substitutes for the career counselor's expert judgment about the intervention sequence, taking into account the client's unique situation and personal traits' (p. 318), and with Osipow (1999) who, referring to Career Decision Making Self-Efficacy Scale (CDMSES) (Taylor & Betz, 1983), emphasizes that it 'can identify those aspects of the career decision-making process itself in which clients may be deficient. Having done that, emphasis in counseling can be placed on helping individuals acquire the skills needed to progress further in their career decision status' (p. 152).…”
Section: 65mentioning
confidence: 62%
“…Gati, Landman, Davidovitch, Asulin‐Peretz, and Gadassi () suggested that individuals may be described more accurately as using a combination of approaches in career decision making and that it may be more informative to consider a broad set of decision dimensions than to focus on broad styles (e.g., avoidant, dependent, rational). Gati et al suggested using the profiles of 11 different decision dimensions. Information gathering reflects the degree of involvement in the collection and organization of information.…”
Section: Decision Strategies In Relation To Decision Difficultiesmentioning
confidence: 99%
“…Gati et al defined these 11 dimensions as “behavioral patterns for dealing with the challenge of making a decision” (p. 286). For the purposes of our investigation, we chose to use the term strategy to refer to these 11 dimensions because they are behavioral plans to achieve a goal.…”
Section: Decision Strategies In Relation To Decision Difficultiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Also several diagnostic systems have been developed (Brown et al, 2012;Gati, Krausz, & Osipow, 1996;Hacker, Carr, Abrams, & Brown, 2013;Saka & Gati, & Kelly, 2008), with Gati and colleagues system used extensively with some success to direct intervention efforts (e.g., Gati & Amir, 2010;Gati & Levin, 2014). Peterson and his colleagues at the Career Center at the Florida State University have been tailoring treatments to client problems for some time via their cognitive information processing theory (Reardon, Lenz, Sampson, & Peterson, 2000), although outcome data on their treatment-matching approach are quite limited.…”
mentioning
confidence: 99%